1986
DOI: 10.1007/bf02387500
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of Wilms' tumor

Abstract: The grey scale ultrasound features of 30 cases of Wilms' tumour examined using a water delay scanner are presented. Eighty-seven percent of masses were of uniform texture, with echogenicity equal to or slightly greater than that of liver with small hypo-echoic areas. There were no totally cystic tumours in the series. In 21 cases the mass was clearly arising from the ipsilateral kidney, but in 9 cases the ipsilateral kidney could not be distinguished from the tumour. The state of the intrahepatic inferior vena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Ultrasonography of the abdomen is extremely useful to confirm the diagnosis [12][13][14] (Table III). It is also a non-invasive, useful diagnostic tool for many general paediatric patients in setting 1.…”
Section: Diagnosis and Differential Diagnosis: Diagnostic Facilities;mentioning
confidence: 99%
“…Ultrasonography of the abdomen is extremely useful to confirm the diagnosis [12][13][14] (Table III). It is also a non-invasive, useful diagnostic tool for many general paediatric patients in setting 1.…”
Section: Diagnosis and Differential Diagnosis: Diagnostic Facilities;mentioning
confidence: 99%
“…Contrast-enhanced CT and non-enhanced MR correctly assessed the tumour origin in all patients. It has been suggested that US can be sufficient as the only imaging modality needed prior to surgery (8,11). The present study indicates that this is not true for large tumours.…”
Section: Discussionmentioning
confidence: 51%
“…Angiography of the vena cava by direct femoral puncture is safe, with no reported cases of tumour embolism. Ultrasound has also proved reliable, but studies suggesting caval occlusion may be caused purely by the weight of tumour pressing on the vessel; under such circumstances, reappraisal in the lateral or prone position may clarify the true diagnosis (De Campo, 1986).…”
Section: The Role Of Surgerymentioning
confidence: 99%